„House Man's Row“ in the principality of Tumanishvilis in the 18 st Century - Marnadze, Rezo (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The paper examines the issue of "House Man's Row" in Georgian principality, specifically, in the Tumanishvili principality. In Georgia, all principality was manage on the basis of ,,House rules“ in the late feudal era. Sometimes, As a result of the divorse of the members of the princely house, distribution of land created a certain controversy between the divisions, which was a abolishof the „House Man's Row“. The „House Man's Row“ was often abolished in the principality of Tumanishvilis in the XVIII Century. Based on existing documentary materials and other historical sources, we can conclude, that the relationship between the members of the princely house of Tumanishvilis was very unstable in the XVIII century.